Exploring Saudi EFL Students’ Attitudes Towards NES and NNES Teachers’ Accents - Bushra Alzahrani; Khulod Alyeaish; Aljoharah Alsalamah; Rahaf Almutairi; Rawan Algahtani (Hasanuddin University, 2022)
Various studies have examined EFL students' attitudes towards accented English. However, this topic has rarely been studied in the Saudi context. The current study examined the attitudes of Saudi EFL university students towards teachers with British or American-accented English (a native speaker model) and Arabic-accented English (a nonnative speaker model) in the language classroom. Thirteen Saudi EFL students participated in this study. An online questionnaire was administered using the matched-guise technique. The results of the study showed that EFL teachers with an American accent is the most favored by their students. Nevertheless, there was little support for this finding. Another important finding is that the examined EFL students had similar positive attitudes towards both British and Arabic accented English. This similarity might suggest that having an accent as an EFL teacher might not perceived negatively as long as the teacher has the ability to deliver information properly.